Sejarah Peristiwa Sumpah Palapa dalam Kitab Pararaton - Dwi Santoso; Ayu Firmaningsih; Deivy Nur Setyowati (SULUK: Jurnal Bahasa, Sastra, dan Budaya, 2020)
This study aims to (1) know the background of Sumpah Palapa event, (2) analyze the value and ideology of Sumpah Palapa, and (3) describe the impact of Sumpah Palapa on the Majapahit Kingdom recorded in the Pararaton Book. This study uses a qualitative research method based on the Pararaton Book which was rewritten by Hardjowadojo (1965). The results of this study are (1) the background of Sumpah Palapa (Amukti Palapa) as a manifestation of Gajah Mada's political policy to invade several regions in the archipelago in order to unite them under the reign of Majapahit, (2) the value and ideology of Sumpah Palapa in the Pararaton Book which are the similarity of the slogan of Bhineka Tunggal Ika, Sumpah Palapa, and Mitreka Satata. All of them are the spirit to unite the diversity of the archipelago in one sovereignty, (3) There are three impacts of Sumpah Palapa recorded in the Pararaton Book namely Bubat War; the cessation of Gajah Mada as Mahapatih Amangkubhumi; and the death of Princess of Sunda who was the future wife Prabu Hayam Wuruk. Overall, it can be seen that the history of Sumpah Palapa event had been recorded in the Pararaton Book and were in accordance with other historical data that become the sources of literature references in this study.